The family next door - Hepworth, Sally (New York : St. Martin's Press, 2018)
"Small, perfect towns often hold the deepest secrets. From the outside, Essies life looks idyllic: a loving husband, a beautiful house in a good neighborhood, and a nearby mother who dotes on her grandchildren. But few of Essies friends know her secret shame: that in a moment of maternal despair, she once walked away from her newborn, asleep in her carriage in a park. Disaster was avoided and Essie got better, but she still fears what lurks inside her, even as her daughter gets older and she has a second baby. When a new woman named Isabelle moves in next door to Essie, she is an immediate object of curiosity in the neighborhood. Why single, when everyone else is married with children? Why renting, when everyone else owns? What mysterious job does she have? And why is she so fascinated with Essie? As the two women grow closer and Essies friends voice their disapproval, it starts to become clear that Isabelles choice of neighborhood was no accident. And that her presence threatens to bring shocking secrets to light."--
Keywords: Motherhood -- Fiction; Female friendship -- Fiction; Women -- Fiction; Neighbors -- Fiction; Thrillers (Fiction).; Domestic fiction